MENGEMBANGKAN PERAN KOMUNITAS PENDAMPING SEBAGAI SUMBER DUKUNGAN SOSIAL BAGI KELUARGA DENGAN ANAK YANG MENGALAMI DISABILITAS - Madyaningrum, Monica Eviandaru; Wijayanto, Murti Hadi; Indrayanti, Maria Irenne (Universitas Sanata Dharma, 2025)
This community service activity aimed to develop the role of peer support groups as a source of social support for families with children experiencing disabilities. The activity was conducted in the form of a capacity-building session for parents who have children with disabilities, organized by the Komunitas Kasih, under the Catholic religious congregation Faithful Companions of Jesus. Preventing the exploitation of children with disabilities was the theme of the capacity-building session. Through presentations by an expert speaker, participants received information about the forms of exploitation of the rights of children with disabilities and steps to prevent it. Participant evaluations indicated that this activity was considered beneficial, as it provided opportunities to connect with families facing similar situations and offered new insights into ways to protect the rights of children with disabilities.